ANALISIS KEAMANAN SISTEM INFORMASI PADA EMAIL CORPORATE UNIVERSITAS TEKNOLOGI SUMBAWA UNTUK IMPLEMENTASI SISTEM KERJA PAPERLESS (INOVASI SMART CAMPUS ) - Juliansyah, Ahmad; Sobirin, Houri; Esabella, Shinta (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
University is an educational unit that plays a role in organizing higher education in advancing science and technology. In order to realize this role, the University must have an adequate data center. This study aims to analyze the security of information systems on corporate email, in order to implement a paperless-based work system at the Sumbawa Technology University, in realizing Smart Campus innovation by the entire Sumbawa Technological University academic community. This study uses a qualitative descriptive research type. By making direct observations about the information system security audit using COBIT 4.1. The results of the research are in the form of a 'Term of Agreement' pact on the integrity of corporate email rules and the implementation of the university's paperless work system innovation.